(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
In order for India's financial system to function, banks are necessary. They provide almost 90% of the country's commercial loans by using more than two-thirds of household savings. Apart from receiving deposits and providing loans, banks also handle a number of other activities, such as financial inclusion, farming, renewable energy, issuing of bonds, foreign currency facilitation, priority sector lending to MSMEs, and numerous other tasks. Any deviation to the proper functioning of banks, which are essential tohandling the monetarystructure of an economy, results in an economic crisis. India was not an exception when it regarding the global financial and economic effects of the economic crisis. That was a significant matteraimed at the developed economies. The problem of the monetary crisis originated in large-scale August 2007 saw defaults in the US sub-prime mortgage market and related markets, which had a severe impact on the country's financial industry before spreading to Europe an effect on the banking segment across the world, including India. The 2008 financial crisis affected the banking sector because it prevented banks from increasing interbank lending, reduced commercial and consumer credit, and cost them money owing to mortgage defaults. This article evaluates the performance of the Indian banking industry by looking at a number of variables, such as total deposits, borrowings, obligations to the banking structure, and more. Before, during, and after the crisis are the three time periods that have been examined. T-tests have fulfilled the analysis's intended purpose. Nevertheless, many challenges were faced during the research, including data scarcity, difficulty gathering data, and ignorance about the early stages of bank operations. However, because it analyses the consequences of the financial crisis using data from a small number of Indian banks to assess how well they performed during the crisis, this work is meant to be helpful to researchers and scholars.